Hubungan Reward And Punishment Dengan Motivasi Belajar Siswa Pada Sekolah Kelas V SD Negeri 098166 Kabupaten Simalungun - Dea Regina Purba; Asister Fernando Siagian; Winarto (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Based on research data, there is still low student learning motivation in class v state elementary school 098166 Simalungun Regency. This is caused by the lack of variety in the methods and media used by teachers so that students feel bored/watching and do not have the enthusiasm to participate in learning in the class. The main objective of this research is: